2007
DOI: 10.1111/j.1365-2826.2007.01583.x
|View full text |Cite
|
Sign up to set email alerts
|

The Type 2 Corticotrophin‐Releasing Hormone Receptor Mediates Orexin A‐Induced Luteinising Hormone Suppression in Ovariectomised Rats

Abstract: Orexins are thought to be regulatory factors of the arousal and sleep patterns. They also affect immune, feeding, autonomic and neuroendocrine systems. We have previously shown that intracerebroventricular (i.c.v.) injection of orexin decreases pulsatile luteinising hormone (LH) secretion in ovariectomised (OVX) rats. However, the details of this mechanism have not been fully examined. Intracerebroventricular injection of orexin A also stimulates corticotrophin-releasing hormone (CRH) systems, which have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…Orexin, which has crucial role in the sleep–wakefulness cycle and appetite control, affects GnRH1 release directly or via the NPY-, CRH-, and β-endorphin-signaling pathways (Li et al, 1999; Tamura et al, 1999; Irahara et al, 2001; Yang et al, 2005; Iwasa et al, 2007). In goldfish, ICV administration of orexin A suppresses spawning behavior, and ICV administration of GnRH2 reduces the level of orexin precursor mRNA in the brain (Hoskins et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Orexin, which has crucial role in the sleep–wakefulness cycle and appetite control, affects GnRH1 release directly or via the NPY-, CRH-, and β-endorphin-signaling pathways (Li et al, 1999; Tamura et al, 1999; Irahara et al, 2001; Yang et al, 2005; Iwasa et al, 2007). In goldfish, ICV administration of orexin A suppresses spawning behavior, and ICV administration of GnRH2 reduces the level of orexin precursor mRNA in the brain (Hoskins et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…injections of GnRH inhibiting factors such as hypocretin (HCRT; also known as orexin) and 2-buten-4-olide suppressed plasma LH levels immediately after injection, with the suppression being sustained for at least 1 h (Saito et al 1993, Kaji et al 1998, Tamura et al 1999, Iwasa et al 2007). Kriegsfeld et al (2006) deduced that RFRP-3 suppresses LH secretion at the hypothalamic level, as more than 40% of the GnRH neurons were projected from the GnIH-immunoreactive fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others have found that the expression levels of kisspeptin and its receptor, which are positive regulators of GnRH, are also sensitive to immune stress (Watanobe and Hayakawa, 2003; Kisney‐Jones et al, 2009). We reported that high dose LPS injection suppressed hypothalamic Kiss1, Kiss1r , and GnRH mRNA expression in female rats (Iwasa et al, 2007; Iwasa et al, 2014). However, the expression levels of these molecules were not affected by the injection of a lower dose of LPS at any examined age in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the HPG axis acquires sensitivity to immune stress around PND25 in rats, which is similar to the age at which the HPA axis becomes sensitive to immune stress (Witek‐Janusek, 1988; Spencer et al, 2006 ). In adulthood, immune stress activates HPA axis (Shanks et al, 1995; Ellis et al, 2006) and induces hypothalamic CRH mRNA expression, which suppresses LH secretion mediated by CRH‐R2 on GnRH neuron (Li et al, 2005, 2006; Iwasa et al, 2007, 2009). Suppressed LH secretion at PND 25 might be related to HPA axis that acquire sensitivity to LPS at PND 21 (Witek‐Janusek, 1988).…”
Section: Discussionmentioning
confidence: 99%